The art of engraving ; a book of instructions - Meek, James B., 1901- (Montezuma, Iowa : F. Brownell, 2011)
Brings the reader - for the first time ever - a complete, authoritative, imaginative and detailed introduction to and training in the art of gun engraving. This book does not assume you know anything about engraving. You start at the beginning by learning to draw scrolls and layouts, then cut practice plates until you are sure enough of your ability to actually proceed to designing a pattern, transferring it to a gun and cutting it into the steel. Whether you want to learn to engrave now ... think you might like to in the future. . . or simply wish to broaden your knowledge of art to be able to better judge the work of others (as you will learn to tell the good from the bad - and know why), this is the book for you.
-- Design and layout -- Materials -- Anatomy -- Lettering -- The camera, another tool -- Beginning to engrave -- Advanced engraving -- The gravermeister.
Includes bibliographical references (page 188) and index.
Keywords: Engraving (Metal-work)